KEMAMPUAN MENULIS AKADEMIK GURU MATA PELAJARAN NON-BAHASA DI JAWA BARAT - Riswanda Setiadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to: (a) assess the academic writing skills of non-language teachers, (b) analyze mistakes in their academic writing test results, and (c) identify factors causingthe difficulties they encounter in developing their academic writing skills. The subjectswere 126 non-language teachers who had participated in the teacher certification programfrom 14 regencies/cities in West Java Province. The findings show that on the whole theiracademic writing mean score is 57.2 of a total score of 100. Referring to an academicwriting assessment scale, the mean score is fairly good. Writing experiences, training, andacademic atmosphere are important factors that have contributions to teachers’ academicwriting skills.